Clinical Significance of Serum Galactose-Deficient IgA1 Level in Children with IgA Nephropathy. (21st May 2020) - Irabu, Hitoshi; Shimizu, Masaki; Kaneko, Shuya; Inoue, Natsumi; Mizuta, Mao; Ohta, Kazuhide; Yachie, Akihiro
Abstract : This study was aimed at investigating the clinical significance of serum galactose-deficient IgA1 (Gd-IgA1) levels measured by a novel lectin-independent enzyme-linked immunosorbent assay (ELISA) using an anti-Gd-IgA1 monoclonal antibody (KM55) as a disease-specific biomarker for IgA nephropathy (IgAN) in children. Thirty-three children with IgAN, 40 with non-IgA glomerular diseases, and 38 age-matched healthy controls (HCs) were enrolled. Serum Gd-IgA1 levels were quantified by ELISA using KM55. Results were statistically compared with clinical features and pathological findings of IgAN. Serum Gd-IgA1 levels were significantly elevated in children with IgAN compared with children with non-IgA glomerular diseases and HCs. Serum Gd-IgA1 levels in children with IgAN were positively correlated with serum total IgA levels. However, the serum Gd-IgA1/total IgA ratio (Gd-IgA1/IgA) was also significantly elevated in children with IgAN. Serum Gd-IgA1 levels in children with IgAN increased in an age-dependent manner. The cutoff value of serum Gd-IgA1 levels for differentiating IgAN from non-IgA glomerular diseases was 3236 in children < 12 years and 5284 in children ≥ 12 years, respectively. In contrast, serum Gd-IgA1/IgA was age-independent. The cutoff value of serum Gd-IgA1/IgA for differentiating IgAN from non-IgA glomerular diseases was 0.2401. Serum Gd-IgA1 levels were negatively correlated with eGFR and positively correlated with mesangial IgA deposition. In contrast, serum Gd-IgA1/IgA levels were not correlated with any clinical parameters of IgAN. In conclusion, serum Gd-IgA1 levels were significantly elevated in children with IgAN. However, those levels were age-dependent; therefore, serum Gd-IgA1 levels classified by age and/or serum Gd-IgA1/IgA might have diagnostic values in children with IgAN.